Os sistemas voltados à gestão empresarial e sua conexão com a indústria 4.0: o papel das tecnologias da empresa SAP - Machado, Etelmir Bitencourt (Universidade do Vale do Rio dos Sinos, 2020)
Industry 4.0 has been around the world for some time, but its concepts have been consolidated since the decade of 2010. The concept addressed in this work was based on Germany's approach, from 2012, where the viability of a more precise production is perceived, of lower cost and, to a certain extent, customizable, but always promising the creation of smart factories, connected to the company's management systems, forming a “single unit”. In the course of the research, based on the DSR methodology, the companies that were studied allowed to confirm the innumerable challenges, listed at first by the literature, that exist for the implementation of the concepts of Industry 4.0 in an organization. These challenges go beyond the technology aspects and expand to organizational culture, integration of system concepts, expansion of suppliers for solutions, in addition to other organizational impacts. The surveyed companies have the characteristics of being in the process of implanting Industry 4.0, but in different stages. However, all of them are Brazilian transformation industries, which have the system of the German company SAP as ERP, which has a set of other technologies to support the implementation of Industry 4.0. Therefore, given the challenges imposed by this Industry 4.0 implementation initiative, with studies carried out in the literature, research carried out in organizations and in the solutions of the SAP company, it was possible to develop a framework (in its first version) that is proposed to help in conducting the implementation of this initiative, where this artifact contemplates, actions to be carried out, technologies to be involved, expected results at each stage and their connections with the next stages, as well as the degree of evolution of some environmental aspects, such as the organizational maturity. With this artifact, managers gain visibility into what each stage of the process must accomplish, as well as being able to perceive the need to break certain cultural concepts or paradigms existing in the organization, as well as allowing the team to have information about the various organizational performance indicators.
Keywords: Indústria 4.0; Tecnologia; Processo; Cultura organizacional; SAP; SAP Leonardo; Industry 4.0; Technology; Process; Organizational culture; Framework; Design science research; ACCNPQ::Ciências Sociais Aplicadas::Administração